Internal stresses and magnetic properties of Fe-Co electrolytic coatings - Proskurina, V.O.; Yermolenko, I.Yu.; Zyubanova, S.I.; Shipkova, I.G.; Avramenko, B.A.; Sachanova, Yu.I. (Functional Materials, 2017)
Consideration was given to the effect of electrolysis parameters on the composition and the properties of electrolytic iron-cobalt film coatings obtained from citrate electrolytes. The interconnection between the film composition and the film thickness with its internal stresses and magnetic properties has been studied. It was established that Fe60Co40 alloys show the lowest level of internal stresses for the saturation induction of 1.8 to 2.1. Tl.